A Remark on the Level Sets of the Graph of Harmonic Functions Bounded by Two Circles in Parallel Planes (Journal of Partial Differential Equations, 2015)
" In this paper,we find two auxiliary functions andmake use of themaximum principle to study the level sets of harmonic function defined on a convex ring with homogeneous Dirichlet boundary conditions in $\\mathbb{R}^2$. In higher dimensions, we also have a similar result to Jagy's."
Keywords: Harmonic function; maximum principle; level set